Preparation method of biomass high-water-absorption gel with bamboo powder as raw material

Through the ultrasonic auxiliary technology, the co -concentration of bamboo powder with sulfonic acid groups and carboxylic acid groups aggregate free radical solutions to form high water absorption gels with network structures, which solves the preparation of high -efficiency water absorption gel in existing technologies. The problem has achieved low -cost and efficient water absorption and maintenance effects.

CN119371611APending Publication Date: 2025-01-28ZHEJIANG FORESTRY UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311589212.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to quickly prepare highly efficient water-absorbing biomass high-water absorption gels, and the process cost is relatively high.

Method used

Using ultrasonic auxiliary technology, the 2-acryl-2-methyl-1-propylene sulfonic acid and acrylic acid with bamboo powder with sulfonic acid groups are used as clustering monomers. Advanced, adding causes and cross -linking agents to form high water absorption gels with network structures.

Benefits of technology

The rapid transformation of bamboo powder to high-efficiency water absorption high-water absorption gels reduced the cost of process, and the maximum water absorption rate of gel in ultra-pure water and rain reached 1047g · G-1 and 952g · G-1. High stability, can be reused at least 5 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371611A_ABST
    Figure CN119371611A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of biomass high-water-absorption gel with bamboo powder as a raw material. The preparation method of the biomass high-water-absorption gel with the bamboo powder as the raw material comprises the following steps that firstly, 60-mesh bamboo powder is mixed with water, ultrasonic treatment is conducted for 1 min, and a bamboo powder mixed solution is prepared; 2, 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS) and acrylic acid (AA) are used as comonomers, and a sodium hydroxide solution is used for neutralization; and 3, uniformly mixing the neutralized monomer with the bamboo powder mixed solution, adding an initiator and a cross-linking agent, carrying out ultrasonic mixing dispersion for 1 min, introducing nitrogen for sweeping and blowing, and carrying out a reaction in an oil bath pan at 60 DEG C for about 20 min so as to obtain the high-water-absorption gel. The prepared super absorbent gel can effectively adsorb moisture, the adsorption capacity of the super absorbent gel to moisture at the room temperature can reach 1047 g / g at most, the bamboo powder is used as the raw material, the production cost is reduced, and the super absorbent gel has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomass super absorbent gel preparation, in particular to a method for preparing biomass super absorbent gel using bamboo powder as a raw material. Background Art

[0002] Biomass superabsorbent gel is a known bio-friendly water-retaining agent. Compared with traditional superabsorbent gel, it has better ability to absorb and retain water and environmental compatibility. Chemical cross-linking is usually more effective in achieving higher water absorption and is used to improve water absorption capacity.

[0003] Bamboo grows fast and has abundant yields. It is a cheap and renewable natural resource. Due to its biodegradability, biocompatibility, low toxicity and the fact that the cellulose it contains is rich in hydroxyl functional groups, it is an ideal raw material for synthesizing polymer materials. Bamboo powder is a promising material for preparing polymer gels. The effect of ultrasound on biomass pretreatment is manifested in the cavitation and mechanical effects produced in the solution, which will impact and shear the biomass surface, thereby effectively destroying the hydrogen bonds in the cellulose molecules and making the biomass rough and irregular. Based on ultrasound assistance, the rapid preparation of biomass highly absorbent gels can be achieved.

[0004] Therefore, it is necessary to provide a new method for preparing a biomass highly absorbent gel using bamboo powder as a raw material to solve the above technical problems. Summary of the invention

[0005] The technical problem solved by the invention is to provide a method for preparing a biomass super absorbent gel using bamboo powder as a raw material, which can realize rapid preparation of the biomass super absorbent gel by ultrasound assistance.

[0006] The method for preparing a biomass highly absorbent gel using bamboo powder as a raw material provided by the present invention comprises the following steps: Step 1: mixing 60-mesh bamboo powder with water, and ultrasonicating for 1 minute to prepare a bamboo powder mixed solution;

[0007] Step 2: Using 2-acrylamido-2-methyl-1-propane sulfonic acid having a sulfonic acid group and acrylic acid as copolymer monomers, neutralizing with a sodium hydroxide solution, wherein 2-acrylamido-2-methyl-1-propane sulfonic acid is referred to as AMPS, acrylic acid is referred to as AA, and the mass ratio of AMPS to AA is 2.5-3:1;

[0008] Step 3: Take the neutralized monomer in step 2 and the bamboo powder mixed solution in step 1 and mix them evenly, the mass ratio of AMPS to the bamboo powder mixed solution is 1-1.2:1; then add initiator and cross-linking agent, ultrasonically mix and disperse for 1 minute, introduce nitrogen for sweeping, react in a 60° C. oil bath for about 30 minutes to polymerize to obtain the highly absorbent gel, and after the reaction is completed, cool, soak, wash, and dry to obtain the target compound, i.e., the biomass highly absorbent gel of bamboo powder and sulfonic acid and carboxylic acid groups;

[0009] The synthetic route of the above reaction is as follows:

[0010]

[0011] Preferably, the mass ratio of the bamboo powder to water in step 1 is 1:20.

[0012] Preferably, the neutralization degree of AMPS in step 2 is 60-80%.

[0013] Preferably, the initiator in step three is ammonium persulfate, and its usage ratio is 0.25-1.25%, and the cross-linking agent is N,N'-methylenebisacrylamide, and its usage ratio is 0.05-0.25%.

[0014] Preferably, the drying temperature in step three is 60°C.

[0015] The biomass superabsorbent gel based on bamboo powder and sulfonic acid and carboxylic acid groups prepared by the preparation method can be used for water absorption and retention.

[0016] The present invention initiates the hydroxyl groups of bamboo powder cellulose into alkoxy free radicals through free radical reaction, polymerizes with sulfonic acid groups and carboxylic acid groups through graft copolymerization, and generates a highly absorbent gel with a network structure under the action of a crosslinking agent, which not only increases the swelling performance of the highly absorbent gel, but also provides hydrogen bonds and electrostatic effects of highly active functional groups for water absorption, and also solves the problem of biocompatibility of the highly absorbent gel in the environment.

[0017] Compared with the prior art, the present invention has the following significant advantages: (1) The preparation method of the highly absorbent gel adopts free radical solution polymerization, the solvent is green and environmentally friendly, the reaction conditions are mild, and the process steps are simplified by combining with ultrasound assistance. In addition, bamboo powder is used as the raw material, and bamboo powder is cheap and easy to obtain, which greatly reduces the process cost; (2) The biomass highly absorbent gel (BASA) with bamboo powder sulfonic acid and carboxylic acid groups prepared by the preparation method can effectively absorb and retain moisture, wherein the maximum water absorption rate of BASA in ultrapure water and rainwater is 1047g·g-1 and 952g·g-1, respectively; (3) The adsorbent has stable adsorption performance. The BASA prepared by the present invention can be reused for at least 5 times, has high stability, and has no obvious change in water retention performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 FTIR spectra of AMPS, AA, BASA, BASA after water absorption and BASA after five cycles of recycling;

[0019] Figure 2 is the SEM-EDS spectrum of BASA;

[0020] Figure 3 The adsorption capacity of BASA under different reaction conditions on different water qualities;

[0021] Figure 4 is the moisture release capacity diagram of BASA at different temperatures;

[0022] Figure 5 This is a test chart of BASA's repeated use of ultrapure water adsorption. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.

[0024] Please refer to Figure 1 , Figure 2 , Figure 3 , Figure 4 and Figure 5 ;

[0025] A method for preparing a biomass highly absorbent gel using bamboo powder as a raw material comprises the following steps:

[0026] Step 1: Weigh 1 g of bamboo powder into a 150 mL round-bottom flask, add 20 mL of pure water, mix and sonicate for 1 min;

[0027] Step 2: Weigh 20.72 g of 2-acrylamido-2-methyl-1-propanesulfonic acid and 7.20 g of acrylic acid respectively into a 100 mL beaker, add 30% by mass NaOH to neutralize in an ice water bath.

[0028] Step 3: Weigh 0.10 g of ammonium persulfate and 0.02 g of N,N'-methylenebisacrylamide and mix them evenly with the solutions in step 1 and step 2, introduce nitrogen, fix in an oil bath, stir at 333 K, heat to react for 15 minutes, stop heating after condensation, cool to room temperature, soak and wash with ethanol for 3 minutes, and dry at 333 K to obtain a biomass highly absorbent gel of bamboo powder and sulfonic acid and carboxylic acid groups.

[0029] The preparation conditions of the biomass super absorbent gel of bamboo powder and sulfonic acid and carboxylic acid groups are single-factor experiments on monomer ratio, neutralization degree, initiator content and cross-linking agent content. The neutralization degree of NaOH is 60-80%, the ratio of AMPS to AA is 2.5-3:1, the mass ratio of AMPS to bamboo powder mixed solution is 1-1.2:1, the amount of N,N'-methylenebisacrylamide accounts for 0.05-0.25% of the total weight of the solution in step three, and the ammonium persulfate accounts for 0.25-1.25% of the total weight of the solution in step three; 20 groups of parallel experiments are set.

[0030] The structural characterization and test results analysis of the bamboo powder and sulfonic acid and carboxylic acid group biomass super absorbent gel (BASA) prepared in the implementation scheme are as follows:

[0031] (1) FTIR

[0032] The infrared characterization of AMPS, AA, BASA, BASA after water absorption and BASA after five cycles is shown in Figure 2. Figure 1 The curves in the figure represent: acrylic acid (a), 2-acrylamido-2-methyl-1-propane sulfonic acid (b), bamboo powder and biomass super absorbent gel of sulfonic acid and carboxylic acid groups (c), BASA after absorbing water once (d) and BASA after recycling 5 times (e).

[0033] The absorption peak at 3400cm-1 is caused by the stretching vibration of -OH and -NH of amide, and the absorption peak at 2900cm-1 is attributed to the stretching vibration of -CH. The absorption peak at 1732cm-1 is due to the C=O of AA, indicating that acrylic acid is grafted onto the hydrogel. The absorption peak at 1645cm-1 is mainly due to the stretching vibration of the C=O of the amide group, and 1115cm-1 and 1043cm-1 are the bending and stretching vibration peaks of the sulfonic acid group S=O, corresponding to the sulfonic acid group of AMPS. The above infrared results show that AMPS and AA are successfully grafted with bamboo powder. The infrared shows that the above hydrophilic groups still exist after BASA absorbs water once (d) and after BASA is recycled 5 times (e), indicating that the hydrophilic groups of the polymer are stable.

[0034] (2) SEM-EDS

[0035] The synthesized hydrogel exhibits a rough and wrinkled surface structure, which facilitates interaction with water molecules and increases water absorption capacity. EDS spectrum shows that the main elements contained in BASA are C, O, N and S, indicating that the grafting of AMPS is successful.

[0036] (3) Adsorption capacity of BASA under different reaction conditions on different water qualities

[0037] Using the filter bag method, accurately weigh 0.1±0.0003g of dry sample and immerse it in 100mL of ultrapure water, tap water, rainwater, lake water and 0.9% NaCl solution. Allow it to absorb water and swell to equilibrium at room temperature, and measure the water absorption rate of the product.

[0038] Figure 3 (a) When the degree of neutralization is 60-70%, the water absorption capacity increases with the increase of the degree of neutralization. The electrostatic repulsion between the sulfonate group (-SO3-) and the carboxylic acid group (-COO-) and the increased concentration of sodium ions increase the osmotic pressure difference between the inside and outside of the polymer, thereby increasing the water absorption capacity of BASA. When the degree of neutralization exceeds 70%, the swelling rate decreases. Too high a degree of neutralization causes the reactivity of AMPS and AA to decrease, and the repulsion between adjacent groups is shielded, resulting in a decrease in water absorption capacity. Figure 3 (b) When the ratio of AMPS to AA is 1.2:1–1:1, the water absorption capacity is basically maintained at a high level, because the grafted -SO3- has better hydrophilicity than -COO-. When the molar ratio of AA is greater than that of AMPS, the water absorption performance decreases, which may be because the graft polymerization mainly occurs on AA, and the reaction amount of AMPS is reduced, thereby reducing the water absorption performance. Figure 3 (c) BASA prepared at 0.05% MBA has the maximum swelling rate. AMPS and AA have high reactivity, and a small amount of MBA can form an effective cross-linked network structure. As the content of cross-linking agent continues to increase, the cross-linking density increases, the space between polymer chains decreases, and the network structure becomes denser, causing the internal space of the network structure to be compressed, making it difficult for water molecules to enter, and reducing the water absorption capacity. As the amount of initiator increases, the change trend of the water absorption rate first increases and then decreases. Figure 3 (d) When the initiator content is 0.5%, the maximum water absorption rate is obtained. The concentration of the initiator will affect the number of free radicals generated in the reaction system. When the initiator concentration is low, the number of free radicals is small, the formed network structure is incomplete, and the gel network of the material is difficult to form. As the amount of initiator increases, excessive free radicals are generated, the probability of collision between bimolecules increases, resulting in the termination of the polymerization reaction, which reduces the kinetic chain length of the polymer and reduces the swelling capacity.

[0039] Moisture release capacity of BASA at different temperatures

[0040] The temperatures of the constant temperature forced air drying oven were set at 35°C, 45°C, 55°C and 65°C, respectively. Three equal portions of the hydrogel at water absorption and swelling equilibrium were weighed into 9-cm diameter culture dishes, and placed in an oven at the set temperature. Samples were taken and the remaining weight was weighed every 2 hours.

[0041] At 35°C, the water retention rate is relatively high at 80.1% after 10 hours, and at 65°C, the water retention rate is 16.8% after 10 hours. On the one hand, water molecules bind to hydrophilic groups such as -SO3H and -COOH, and there is an interaction force, which inhibits the movement of water molecules. On the other hand, hydrogen bonds are formed between water molecules and the water retaining agent BASA, which fixes the water molecules in the cross-linked network structure of the material and inhibits the loss of water molecules. At higher temperatures, the movement of water molecules is accelerated, these binding forces are weakened, and the water retention capacity decreases.

[0042] (5) Reuse of BASA adsorption on ultrapure water

[0043] 1.0 g BASA was immersed in a beaker containing 2000 mL of water to allow the highly absorbent gel to swell to equilibrium, and then placed in a constant temperature forced air drying oven at 60°C to dry. Ultrapure water was added to the dried sample to test the recycling performance of the water retaining agent.

[0044] At 35°C, the water retention rate is relatively high at 80.1% after 10 hours, and at 65°C, the water retention rate is 16.8% after 10 hours. On the one hand, water molecules bind to hydrophilic groups such as -SO3H and -COOH, and there is an interaction force, which inhibits the movement of water molecules. On the other hand, hydrogen bonds are formed between water molecules and the water retaining agent BASA, which fixes the water molecules in the cross-linked network structure of the material and inhibits the loss of water molecules. At higher temperatures, the movement of water molecules is accelerated, these binding forces are weakened, and the water retention capacity decreases.

[0045] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a biomass highly absorbent gel using bamboo powder as raw material, characterized in that: The following steps are involved: Step 1: Mix 60-mesh bamboo powder with water and ultrasonicate for 1 minute to prepare bamboo powder mixed solution; Step 2: Using 2-acrylamido-2-methyl-1-propane sulfonic acid having a sulfonic acid group and acrylic acid as copolymer monomers, neutralizing with a sodium hydroxide solution, wherein 2-acrylamido-2-methyl-1-propane sulfonic acid is referred to as AMPS, acrylic acid is referred to as AA, and the mass ratio of AMPS to AA is 2.5-3:1; Step 3: Take the neutralized monomer in step 2 and the bamboo powder mixed solution in step 1 and mix them evenly, the mass ratio of AMPS to the bamboo powder mixed solution is 1-1.2:1; then add initiator and cross-linking agent, ultrasonically mix and disperse for 1 minute, introduce nitrogen for sweeping, react in a 60°C oil bath for about 30 minutes to polymerize to obtain the highly absorbent gel, and after the reaction is completed, cool, soak, wash, and dry to obtain the target compound, that is, the biomass highly absorbent gel of bamboo powder and sulfonic acid and carboxylic acid groups.

2. The method for preparing biomass highly absorbent gel using bamboo powder as raw material according to claim 1, characterized in that: The mass ratio of bamboo powder to water described in step 1 is 1:

20.

3. The method for preparing biomass highly absorbent gel using bamboo powder as raw material according to claim 1, characterized in that: The neutralization degree of AMPS in step 2 is 60-80%.

4. The method for preparing biomass highly absorbent gel using bamboo powder as raw material according to claim 1, characterized in that: The initiator in step three is ammonium persulfate, and its usage ratio is 0.25-1.25%. The cross-linking agent is N,N'-methylenebisacrylamide, and its usage ratio is 0.05-0.25%.

5. The method for preparing biomass highly absorbent gel using bamboo powder as raw material according to claim 1, characterized in that: The drying temperature described in step 3 is 60°C.

Citation Information

Cited By

  • Preparation method of carboxymethylated bamboo powder multifunctional intelligent response hydrogel material

    CN119978262A